Calibration Methods of Atmospheric Aerosol Lidar and a Case Study of Haze Process - Chen, Chao; Song, Xiaoquan; Wang, Zhangjun; Chen, Yubao; Wang, Xiaopeng; Bu, Zhichao; Zhang, Xi; Zhuang, Quanfeng; Pan, Xin; Li, Hui; Zhang, Feng; Wang, Xiufen; et al. (Frontiers in Physics, 2022)
Lidar is a reliable tool for active remote sensing detection of atmospheric aerosols. A multi-wavelength aerosol lidar (MWAL) with 355 nm, 532 nm and 1064 nm as detection light sources has been developed and deployed for operational observations at Haidian District Meteorological Service of Beijing. The structure design, specifications, observation campaign and detection principle of the MWAL are introduced. To ensure the accuracy and reliability of the lidar observation data, the calibration contents and methods of lidar are proposed, including the correction and gluing of the original data, the collimation of the transmitting and receiving optical axes, the testing of signal saturation, the correction of molecular Rayleigh fitting and the determination of the depolarization ratio correction factor. Finally, a haze process from September 29 to October 2, 2019 was observed and analyzed using the data of lidar, digital radiosonde, air quality and relative humidity observed by the Haidian District Meteorological Service. The detection results show the reliability of lidar which can effectively obtain the temporal and spatial variation characteristics of the haze. The profiles of aerosol extinction coefficient, potential temperature and relative humidity can be effectively used to analyze the haze thickness and the influence of relative humidity on aerosol particles. The data of air quality monitor shows that PM10 is the main pollutant and the ratio of PM2.5/PM10 is negatively correlated with relative humidity. Finally, the HYSPLIT trajectory tracking model of the National Oceanic and Atmospheric Administration (NOAA) is used to further study the source of pollutants in this haze process.